OPTIMIZING ANTIBIOTIC USE USING ARTIFICIAL INTELLIGENCE IN TRANSFORMING HEALTHCARE - Kelvin Smith (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
Artificial intelligence (AI) offers innovative solutions to the increasing issue of antibiotic resistance and enhances patient outcomes, which has the potential to drastically change healthcare's efforts to steward antibiotics. This study examines the various applications of AI in antibiotic stewardship, such as predictive analytics for resistance patterns, treatment recommendations, monitoring treatment response, and diagnostic decision support. It also discusses the challenges and ethical dilemmas surrounding the use of AI in clinical contexts, such as power imbalances in the medical industry, algorithmic bias, data infrastructure, and patient privacy. Despite these challenges, there is hope for the future of AI-powered antibiotic stewardship. Opportunities exist for collaboration and innovation in real-time data analytics, digital health platforms, telemedicine solutions, interoperable AI ecosystems, and diverse approaches that combine AI with other state-of-the-art technologies. By implementing AI technologies appropriately and ethically, healthcare systems may fully leverage AI to optimize antibiotic use, combat antibiotic resistance, and enhance patient outcomes globally.